Biological Environmental Conditions on the Incidence of Dengue Hemorrhagic Fever - Fidiariani Sjaaf; Anita Darmayanti; Mutiara Anissa; Ninik Dwi Ambarwati; Agung Sutriyawan (Jurnal Ilmiah Kesehatan (JIKA), 2023)
An infectious disease that is still a problem in the city of Bandung is dengue hemorrhagic fever which is transmitted through the vector aedes aegipty. The purpose of this study was to analyze the influence of biological environment on the incidence of dengue hemorrhagic fever. The design used was a control case. The subjects of this study were dengue hemorrhagic fever sufferers in the Sekejati Health Center work area. The sample size was 180 subjects and was taken using a simple random. The study sample consisted of 90 cases and 90 controls. Data were collected by direct observation using observation sheets. Data were analyzed using the chi-square test. The results showed that the variables that affect the incidence of dengue hemorrhagic fever are the presence of breeding place (p-value=0,001 and POR=3,2), Resting place (p-value=0,011 and POR=2,2), solid waste (p-value=0,033 and POR=2,0), and mosquito repellent plants (p-value=0,012 and POR=2,5). The biological environment that is resistant to dengue hemorrhagic fever is a breeding place, resting place, the presence of solid waste, and mosquito repellent plants. It is recommended for health workers to be more active in conducting socialization to the community regarding efforts to prevent dengue hemorrhagic fever.